The Deportation of Refugees and Illegal Immigrants: A Sociocultural Study - Sigit Apriyanto; Adelina Anum (Journal of Social Science and Humanities, 2025)
The deportation of refugees and illegal immigrants is a complex issue involving legal, human rights, and socio-cultural impacts in both the receiving and origin countries. This study examined the phenomenon of refugee and illegal immigrant deportation and its social and cultural effects, focusing on cultural identity, social marginalisation, and the economic conditions of deported individuals. The research employs a qualitative approach by analysing literature from various sources, such as journals and books, from a sociocultural perspective. The findings reveal that deportation causes profound social dislocation, severing social and economic ties established in the host country, and exacerbating social marginalisation and cultural identity crises. In the home country, deported individuals often face social stigma, which hinders reintegration. Additionally, deportation disrupts the economic networks built in the host country. The study concludes that more humane policies and social reintegration support for deported individuals are essential.